2012
DOI: 10.1007/s00253-012-4272-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial population dynamics and proteomics in membrane bioreactors with enzymatic quorum quenching

Abstract: Quorum sensing gives rise to biofilm formation on the membrane surface, which in turn causes a loss of water permeability in membrane bioreactors (MBRs) for wastewater treatment. Enzymatic quorum quenching was reported to successfully inhibit the formation of biofilm in MBRs through the decomposition of signal molecules, N-acyl homoserine lactones (AHLs). The aim of this study was to elucidate the mechanisms of quorum quenching in more detail in terms of microbial population dynamics and proteomics. Microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Similar approach was attempted by Kim et al [21] using pre-isolated strain [16] and found significant reduction in the development of communities responsible for sensing mechanism. Kim et al [19], incorporated Rhodococcus sp.…”
Section: Introductionmentioning
confidence: 82%
“…Similar approach was attempted by Kim et al [21] using pre-isolated strain [16] and found significant reduction in the development of communities responsible for sensing mechanism. Kim et al [19], incorporated Rhodococcus sp.…”
Section: Introductionmentioning
confidence: 82%
“…Excessive growth of biofilms and associated EPS would also greatly limit the diffusion of substrates and nutrients to the cells 19,20 . Consequently, the cells in the inner layers of biofilm would become less active.…”
Section: Introductionmentioning
confidence: 99%
“…cyclic di-guanosine monophosphate (c-di-GMP)) that regulate biofilm development 26–28 , and peptide that reduces stress responsive guanosine pentaphosphate (ppGpp) concentration 29 . Other biological methods also include quorum quenching that interrupts autoinducer-mediated quorum sensing 20,30 and controlling the production of adhesive proteins such as csgA which could inhibit initial attachment of the bacteria 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The robust biofilms are needed for treatment of wastewater by trickling filters, granular sludge and moving bed biofilm reactors 6, 80. However, deposition of biofilms and associated extracellular polysaccharides (EPS) on membrane surfaces decreases filtration flux and causes permeability loss 81, 82. The non-degraded organic matters, microbial flocs and SMP are also considered as potential foulants 83, 84, but the formation of biofilms on membrane surfaces is the major contributor in membrane biofouling and is the main obstacle restricting the development of MBR technology for advanced wastewater treatment.…”
Section: Quorum Sensing and Biofoulingmentioning
confidence: 99%
“…In addition to this, several studies have linked presence of AHLs with biofilm formation and addressed the problem of membrane biofouling in MBRs 82, 89, 92. The chromatographic analysis of MBR sludge using HPLC technique has identified the presence of several AHLs molecules.…”
Section: Quorum Sensing and Biofoulingmentioning
confidence: 99%